2002
DOI: 10.1002/etc.5620210724
|View full text |Cite
|
Sign up to set email alerts
|

Increased toxicity to invertebrates associated with a mixture of atrazine and organophosphate insecticides

Abstract: This study examined the joint toxicity of atrazine and three organophosphate (OP) insecticides (chlorpyrifos, methyl parathion, and diazinon) exposed to Hyalella azteca and Musca domestica. A factorial design was used to evaluate the toxicity of binary mixtures in which the lethal concentration/lethal dose (LC1/LD1, LC5/LD5, LC15/LD15, and LC50/LD50) of each OP was combined with atrazine concentrations of 0, 10, 40, 80, and 200 microg/L for H. azteca and 0, 200, and 2,000 ng/mg for M. domestica. Atrazine conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(53 citation statements)
references
References 27 publications
2
46
0
4
Order By: Relevance
“…greatest decreases at lower doses. This is in accordance with work that suggested other insect P450s are unaffected by atrazine (Anderson and Lydy, 2002).…”
Section: Carbamate Insecticidessupporting
confidence: 93%
“…greatest decreases at lower doses. This is in accordance with work that suggested other insect P450s are unaffected by atrazine (Anderson and Lydy, 2002).…”
Section: Carbamate Insecticidessupporting
confidence: 93%
“…Other studies have shown that the herbicide atrazine, when present at concentrations above 40 µg/L, increases the toxicity of the organophosphate insecticides chlorpyrifos ( fig. 6-21) and diazinon to aquatic invertebrates (Belden and Lydy, 2000;Anderson and Lydy, 2002). Note that atrazine itself is not acutely toxic to these invertebrates, even at high concentrations in water.…”
Section: Conceptual Models Of Mixture Effectsmentioning
confidence: 99%
“…It is used to control a variety of annual broadleaf and grassy weeds and is extensively applied to corn and various silage crops. Its mode of action is based on the inhibition of photosystem I, resulting in the repression of the electron transport mechanisms required for photosysnthesis [91]. Several studies employing Chironomus tentans have demonstrated synergism between triazine insecticides such as atrazine and various OPs such as chlorpirifos [84,[92][93][94].…”
Section: Op Plus Triazinesmentioning
confidence: 99%
“…Several studies of the same genera involving biomarkers measurements have facilitated a better understand of these mechanisms. The study of Anderson and Lydy [91] examined the joint toxicity to H. azteca of atrazine and three OP insecticides (chlorpyrifos, methyl parathion, and diazinon) and found that 200 mg/L atrazine (which alone did not inhibit AChE) in combination with LC10 of each OPs, increasing AChE inhibition to 61, 49, and 43% for chlorpyrifos, methyl parathion, and diazinon, respectively, compared to 41, 12, and 27% for the respective OP dosed individually. Similarly, Jin-Clark et al [45] studied the joint toxicity of the herbicides atrazine and cyanazine with the OP chlorpyrifos on the midge Chironomus tentans, observing a synergistic effect of the herbicides on the toxicity of chlorpyrifos that was associated with an increase of inhibition of AChE.…”
Section: Op Plus Triazinesmentioning
confidence: 99%